A Comparative Study Examining Academic Cohorts with Transnational Migratory Intentions Towards Canada and Australia. (16th May 2016) - Hopkins, John
Abstract: This research examines the issue of transnational academic mobility of academic staff, those choosing to migrate to higher education institutions in different countries as part of their career development, and performs a comparative study between the characteristics of academics examining Australia as a possible migratory destination with those considering Canada. A combination of Google Analytics and two online questionnaires, running in parallel for a period of 12 months, were employed in capturing a range of rich primary quantitative and qualitative research data. Quantitative web analytics data is analysed to locate the geographic origins of migratory interest, with qualitative survey data providing further insight into the academics' background, qualifications, disciplines and reasons for wanting to migrate. When combined, this mixed‐method approach is able to utilise the merged data to develop a detailed profile of academics with migratory intentions towards Australia and Canada, enabling comparisons between the two cohorts to be made.